ANALISIS AWAL KEBAKARAN TANGKI 36 T-102 PERTALITE PADA KAWASAN REFINERY UNIT IV CILACAP – JAWA TENGAH - Budi Utama; Wayan Suparta; Dulhadi Dulhadi (KURVATEK, 2022)
This paper analyzes an induced lightning strike which is thought to have caused a fire in tank 36 T-102 (containing pertalite) at Pertamina refinery unit IV Cilacap – Central Java. This tank fire incident occurred when heavy rain was accompanied by a thunderstorm, on Saturday, November 13, 2021. The statement issued by BMKG that the fire occurred was caused by the phenomenon of lightning induction to the pertalite fuel storage tank, namely lightning induction at the first point a distance of 45 km and at the second point is 12 km. The analysis was carried out by simulation using the Matlab program which was oriented to determine the lightning induced voltage that invades the metal structure of the tank and compares it with the ignition voltage of the 36 T-102 tank. As an indicator parameter for the occurrence of ignition of flammable fuel, simulations of lightning induced voltages as far as 120 meters are also carried out for comparison parameters. The simulation results with comparison indicators revealed that there was a fire in the pertalite fuel tank in tank 36 T-102 it is not caused by lightning strikes as far as 45 km and as farl as 12 km but possibly due to induced lightning strikes in an area as far of hundreds of meters, the sample comparison indicator as far as 120 meters.